Morphological assessment of the North Eurasian interspecific hybrid forms of the genus Bythotrephes Leydig, 1860 (Crustacea: Cladocera: Cercopagididae) - Korovchinsky, Nikolai M. (Zootaxa, 2019)
The North Eurasian interspecific hybrid forms of the genus Bythotrephes Leydig, 1860 are described morphologically in detail with consideration of the previous data on their allozyme analysis and brief morphological examination. In total, three hybrid forms have been encountered, among which B. brevimanus x B. cederströmii appear to be most common and widespread whereas two others, one of which is new to science, are known from single localities. The high morphological variability of the former hybrid form is analyzed and its diagnostic features, distinguishing their representatives from those of parental species are determined. Within their vast range, the hybrids B. brevimanus x B. cederströmii seem to be one of the most common and numerous members of the genus. For instance, they dominate in all reservoirs of the Volga River where their biology was investigated in some detail. The hybrids are distributed widely being known from Sweden, Finland, and north-west of European Russia to Central Yakutia in Eastern Siberia. The southern borders of their range extend to the south of Eastern Siberia and Eastern Kazakhstan. Further more detailed investigations of hybrids, both genetic and morphological, are highly desirable.